2014
DOI: 10.1007/s11096-014-9959-0
|View full text |Cite
|
Sign up to set email alerts
|

Therapeutic monitoring of pediatric renal transplant patients with conversion to generic cyclosporin

Abstract: Conversion of cyclosporin from innovator brand to generic in pediatric renal transplant patients needs to be closely monitored.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
5
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 8 publications
(5 citation statements)
references
References 30 publications
0
5
0
Order By: Relevance
“…This Program supplies, free of charge, to those patients who are in need, with the immunosuppressant drug product depending on the winning bid established by the government. Although we do not have the reliable registry of the brand that patients received, tacrolimus TDM in pediatric transplant patients undergoing immunosuppressant substitution is essential to ensure safety and efficacy of the immunosuppressive treatment, as previously reported for this population 72 . All patients had close clinical and pharmacological monitoring of…”
Section: A C C E P T E Dmentioning
confidence: 99%
“…This Program supplies, free of charge, to those patients who are in need, with the immunosuppressant drug product depending on the winning bid established by the government. Although we do not have the reliable registry of the brand that patients received, tacrolimus TDM in pediatric transplant patients undergoing immunosuppressant substitution is essential to ensure safety and efficacy of the immunosuppressive treatment, as previously reported for this population 72 . All patients had close clinical and pharmacological monitoring of…”
Section: A C C E P T E Dmentioning
confidence: 99%
“…In contrast, the literature on generic substitution for the treatment of more common conditions is extensive and includes reports of adverse outcomes associated with the switch from branded to generic products in a variety of therapeutic areas, especially when NTI drugs are involved [2,5,4,3,66]. Indeed, problems with generic substitution have been reported more consistently with certain drug classes including levothyroxine, post-transplantation immunosuppressants, anti-epileptic drugs, and antidepressants [67,2,68,69,3]. These reports have prompted additional bioequivalence studies, have often resulted in the withdrawal of the generic product, and have led several authors to recommend caution in the use of generics for certain conditions and patient populations.…”
Section: Problematic Generic Substitutionsmentioning
confidence: 99%
“…35 The optimal blood levels of immunosuppressants for patients with transplants differ according to (і) the type of organ transplanted; (іі) the type of the therapy (i.e., monotherapy or combination therapy with other immunosuppressants); and (ііі) the aim of the treatment (induction or maintenance). Moreover, the transition from innovator to generic medications for cost-saving purposes caused serious side effects, especially in pediatric solid organ transplant recipients due to significant variations in the total integrated area under the plasma drug concentration-time curve (AUC), for example, the AUC 0-12h for the first 12 h after injection, making close TDM essential, 36 Thus, for one of the most widely used immunosuppressants for organ transplantation, cyclosporine, a study reported a 16.7% drop of the AUC and a 13.1% drop of the 2-h concentration after oral administration when switching from innovator drug to generic cyclosporine, 37 indicating a reduced bioavailability of the generic drug, which could be associated with treatment failure (= organ rejection) or the need for more frequent dosing. For tacrolimus, another widely used calcineurin inhibitor (i.e., a drug that inhibits the T-cells of the immune system), it was found that patients with identical C 0 may have very different AUC 0-12h , which explains differences in treatment efficacy.…”
Section: Patients With Organ Transplants: Immunosuppressantsmentioning
confidence: 99%